Suplementasi Somatotropin Untuk Memperbaiki Performan Tubuh Tikus Umur 6 Bulan dan 1 Tahun - La Eddy (Universitas Syiah Kuala, 2010)
Aging is associated with a decrease in somatotropin or growth hormone (GH) secretion by anterior pituitary. Somatotropin affects the growth of somatic cells. The objective of this experiment was to study the effects of somatotropin suplementation on body performances of aged male rats. The experimental rats were assigned into a randomized block design with a factorial arrangement. The first factor was age with 2 levels (6 months and 1 year).The second factor was dosage of somatotropin injection with 2 levels (0 and 9 mg/kg BW day). The third factor was the duration of somatotropin injection with 2 levels (3 and 6 weeks). The fourth factor was time of slaughtering after somatotropin injection with 2 levels (1 and 14 days). Parameters measured were body weight, food consumption, total protein, total fat. The result showed that somatotropin has significant effects on body weight, food consumption, total protein, total fat. It is concluded that somatotropin can body performance of six-months and one-year old male rats.